Assessment Standard for the International Classification of Functioning, Disability and Health Rehabilitation Set (I) - Tiebin YAN; Yan GAO; Malan ZHANG; Liming YOU (康复学报)
For further use utilization of the international classification of functioning, disability and health rehabilitation set, the expertise group combined literature research, based on relevant fundamental principles to formulate assessment standard for"the International Classification of Functioning, Disability and Health Rehabilitation Set".The standard consist of 30 categories including 9 body functions,14 activities,7 participations. The standard describes detail of the basis of preparation, scope of application, composition of items, evaluation of results, criteria assessment, application under specific conditions, and precautions for use. It can be applied to evaluate the function of rehabilitation on patients, analyze rehabilitation needs and direct clinical practice.